2011
DOI: 10.1002/stem.642
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the Biphasic Nature of Hypoxia-Induced Motogenic Action in Bone Marrow-Derived Human Mesenchymal Stem Cells

Abstract: Hypoxic conditions have been reported to facilitate preservation of undifferentiated mesenchymal stem cell (MSC) phenotype and positively affect their colony-forming potential, proliferation, and migration/mobilization. In this study, designed to dissect mechanisms underlying hypoxia-dependent migration of bone marrow-derived human MSC (hMSC), signal transduction, and molecular mechanisms were evaluated by integrating morphological, molecular, and cell biology techniques, including the wound healing assay (WHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 47 publications
6
28
0
Order By: Relevance
“…4A). This result corroborates well with the critical role of VEGF in regulating chemotaxis of MSCs into wound bed as reported by several other studies [15], [31], [34][37]. Therefore, further experiments were designed in vitro to evaluate the role of DA on VEGF induced migration of murine MSCs.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…4A). This result corroborates well with the critical role of VEGF in regulating chemotaxis of MSCs into wound bed as reported by several other studies [15], [31], [34][37]. Therefore, further experiments were designed in vitro to evaluate the role of DA on VEGF induced migration of murine MSCs.…”
Section: Resultssupporting
confidence: 90%
“…Several recent reports have indicated that VEGF is the predominant growth factor, which regulates wound angiogenesis [30]–[33] and chemotactic migration of MSCs both in vitro and in vivo [14], [15], [31], [34][37], therefore further experiments were designed in vitro to determine the direct effect of VEGF on the migration of murine MSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors consider short-term hypoxic exposure of MSCs to be permanently maintained under ambient O 2 (20%) as oxidative stress, which may cause functional impairment due to increased ROS production [Guzy and Schumacker, 2006;Zhang et al, 2009;Busletta et al, 2011;Peterson et al, 2011] in part triggered by a significant increase in prooxidants, such as the ROS producer NAD(P)H oxidase subunits p67phox and p47phox [Peterson et al, 2011]. A decrease in activity of the antioxidant enzyme catalase, a major metaboliser of ROS, without changes in SOD and SOD subunit levels confirmed that the metabolism of ROS was also impaired (or at least not sufficient) [Peterson et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Under hypoxic conditions, MSC’s are rapidly mobilized 83,84 and are stimulated to secret increased levels of cytokines involved in tissue growth and angiogenesis 32,85 . In fact preconditioning MSC’s in hypoxia has been shown to enhance their tissue regenerative properties 84,86 .…”
Section: Mesenchymal Stem Cells and Wound Healingmentioning
confidence: 99%